2018
DOI: 10.1002/qua.25627
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the protein and DFT method on the broken‐symmetry and spin states in nitrogenase

Abstract: The enzyme nitrogenase contains a complicated MoFe7CS9 cofactor with 35 possible broken‐symmetry (BS) states. We have studied how the energies of these states depend on the geometry, the surrounding protein, the DFT functional and the basis set, studying the resting state, a one‐electron reduced state and a protonated state. We find that the effect of the basis set is small, up to 11 kJ/mol. Likewise, the effect of the surrounding protein is restricted, up to 10 and 7 kJ/mol for the electrostatic and van der W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
117
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(126 citation statements)
references
References 60 publications
8
117
1
Order By: Relevance
“…7 The setup of the protein is identical to that of our previous studies. [29][30][31] The entire heterotetramer was included in the calculations and the DFT calculations were concentrated on the FeMo cluster in the C subunit. The P clusters and the FeMo cluster in subunit A were modelled by MM in the fully reduced and resting states, respectively.…”
Section: The Proteinmentioning
confidence: 99%
See 2 more Smart Citations
“…7 The setup of the protein is identical to that of our previous studies. [29][30][31] The entire heterotetramer was included in the calculations and the DFT calculations were concentrated on the FeMo cluster in the C subunit. The P clusters and the FeMo cluster in subunit A were modelled by MM in the fully reduced and resting states, respectively.…”
Section: The Proteinmentioning
confidence: 99%
“…All calculations employed the def2-SV(P) basis set, 39 because previous studies have shown that increasing the basis set to def2-TZVPD changes the relative energies by less than 16 kJ mol À1 . 29,31 The calculations were sped up by expanding the Coulomb interactions in an auxiliary basis set, the resolution-of-identity approximation. 59,60 Empirical dispersion corrections were included with the DFT-D3 approach 61 and Becke-Johnson damping, 62 using parameters optimised for each DFT method, as implemented in Turbomole for all functionals except M06, M06-L, M06-2X and M06-HF (for which no parameters are available because the methods should include dispersion effects by parameterisation).…”
Section: Qm Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is equivalent to the broken symmetry (BS) electronic state description [67,68], based on the up/down character of spins on each Fe atom. With the assumption of C3 symmetry for FeMo-co there are 10 BS states, but with the actual C1 symmetry there are 35 BS possibilities [58], and this is the number of possible spinsets for the hydrogenated forms of FeMo-co. There are four stable conformations for an H atom bound to S3B, shown in Scheme 1 panel D. In each of these S3B has pyramidal three-fold coordination, because one of the S3B-Fe interactions is elongated (usually to more than 2.7 Å).…”
Section: The Electronic States Of Femo-co and Its Ligated Formsmentioning
confidence: 99%
“…With eight transition metals, the electronic structure of FeMo-co is complex. Each net spin (S) state possesses 35 electronic states [58,64], as do the various hydrogenated forms [51]. Therefore, descriptions of the possibilities for hydrogenated FeMo-co are essentially maps of geometry, electronic state, and relative energy.…”
Section: Introductionmentioning
confidence: 99%